Obesity Associated With Active, but Preserved Joints in Rheumatoid Arthritis: Results From our National Registry - Fikriye Figen AYHAN,; Şebnem ATAMAN,; Aylin REZVANİ,; Nurdan PAKER,; Nurettin TAŞTEKİN,; Taciser KAYA,; Hatice BODUR,; Mahmut YENER,; Pelin YAZGAN,; Beril DOĞU,; Alev GÜRGAN, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the prevalence of obesity in patients with rheumatoid arthritis (RA) and associations with disease outcomes. Patients and methods: The study population comprised of 1,038 patients with RA (198 males, 840 females; mean age 56.1±12.6 years; range 19 to 94 years) who had been included in National RA-Registry. RA disease activity measures, physical function, quality of life, joint destruction, laboratory tests, as well as pain, fatigue, general health, and patient and physician global health assessments on a visual analog scale were collected. Results: Our patients had established RA with mean disease duration of 10.2±8.8 years and moderate disease activity (disease activity score in 28 joints: mean 3.7±1.6). According to the body mass index (BMI), 70% of the patients were overweight (n=362, 34.9%) or obese (n=364, 35.1%). These patients had higher disease activity scores in 28 joints, visual analog scale-pain and visual analog scale-patient global scores, and higher levels of fasting blood glucose; however, they had lower radiographic scores than normal-BMI patients (p<0.05). Regression analyses showed that the BMI was independently and inversely associated with disease activity scores in 28 joints and Sharp/van der Heijde scores after the adjustments for biologic and treatment-related factors (p<0.05). Conclusion: Our findings indicate that obesity is more common in patients with RA than the general population. High disease activity and low radiographic damage were associated with high BMI in this National RA-Registry.